PENGORGANISASIAN PKBM SARI KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Wildan Bastian Bastian; Said Suhil Achmad Suhil Achmad; Murni Baheram Baheram (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstarct: The purpose of this study was to determine the organizing principle of CLC Sari Tassel Coastal District of the city of Pekanbaru, namely: (i) the purpose of the organization, (ii) organizing the division of labor, (iii) the responsibility of the organizing authority, (iv) coordination, focus of the study include aspects where (place), actors (actor), and activity (activity) performed by CLC Sari Tassel Coastal District of the city of Pekanbaru.This study used a qualitative research method of this type of ethnography, ethnography is to describe culture as such or seek buadaya theme.Informants in this study is the leaders of the CLC Sari as an informant core, administrative staff as informants control, and tutors as key informants. As for how to collect the data is by using the method of observation, interviews, and documentation.Collecting and analyzing data using Spradley models are: (1) the domain analysis, (2) analysis of taxonomy, (3) analysis komponensial and (4) analysis of the cultural theme. In accordance with the appropriate discussion and research purposes, it can be concluded: 1). The aim is to explore the potential of community organizing in learning needs, foster interest in learning to the learners as well as take advantage of the potential that exists within themselves wrga learning. 2). The division of labor is the organizing institution leaders CLC Sari divide the work in accordance with their expertise and their functions. 3). Responsibility in organizing authority is the leader of the institution determines that the program will be held in accordance with the needs of the learners. 4). Coordination is a leader in organizing CLC Sari organize and plan all the programs on the CLC and assisted by the members. 5). Responsibilities in the organization are administrative staff and tutors are given the task of taking care of correspondence and teaching. 6). Labor discipline in the organization are the actors who have been given the task of carrying out their duties properly. 7). Motivation in the organization are the actors provide motivation among fellow members and residents to learn. Key word: The purpose of organizing, division of labor organizing, authority responsibility in organizing and coordination in organizing